1997
DOI: 10.1016/s0167-6296(96)00508-5
|View full text |Cite
|
Sign up to set email alerts
|

Health utility indices and equity considerations

Abstract: The aim of this paper is to propose methods that incorporate equity concerns into cost utility analysis. The focus of the paper is on QALYs. but the results apply to health utility indices in general. Two interpretations of QALYs are considered: QALYs as (yon Neunmnn Morgenstem) utilities and QALYs as measures of health. A justification is provided for aggregating consistently .scaled "'QALYs as utilities" over individuals. The conditions underlying unweighted aggregation of QALYs are identified. These conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
11

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 47 publications
1
49
0
11
Order By: Relevance
“…Bleichrodt (1997) suggested the extension of rank-dependent utility theory from decision under risk to social decision making, by giving different weights to different individuals or outcomes, in a similar fashion as assigning decision weights to probabilities in decisions under risk. Subsequently, Bleichrodt et al (2004) pointed out that it may be unnecessarily restrictive to model aversion to health inequality solely through a concave utility function, and showed that the rank-dependent approach is consistent with the most popular HRSWFs, including those used by Dolan (1998).…”
Section: Introductionmentioning
confidence: 99%
“…Bleichrodt (1997) suggested the extension of rank-dependent utility theory from decision under risk to social decision making, by giving different weights to different individuals or outcomes, in a similar fashion as assigning decision weights to probabilities in decisions under risk. Subsequently, Bleichrodt et al (2004) pointed out that it may be unnecessarily restrictive to model aversion to health inequality solely through a concave utility function, and showed that the rank-dependent approach is consistent with the most popular HRSWFs, including those used by Dolan (1998).…”
Section: Introductionmentioning
confidence: 99%
“…We shall refer to those distributions as population health distributions. We, however, departure from earlier contributions within the health-economics literature, to deal with the evaluation of health distributions, which presume an implicit relationship between the two dimensions at the individual level (e.g., Bleichrodt, 1995Bleichrodt, , 1997Østerdal, 2005;Bleichrodt et al, 2004;Doctor et al, 2009). In other words, we do not assume from the outset the existence of an index summarizing the information of each duplet.…”
Section: Introductionmentioning
confidence: 94%
“…Economists, practitioners and social scientists alike have long been concerned with this issue. Attempts to develop appealing measures to evaluate the health of a population abound in the literature (e.g., Pliskin et al, 1980;Torrance, 1986;Mehrez and Gafni, 1989;Wagstaff, 1991;Bleichrodt, 1995Bleichrodt, , 1997 Williams, 1997; Dolan, 1998 The purpose of this paper is to take the axiomatic approach to the evaluation of population health, a somewhat unexplored approach in the health economics literature, in contrast to many other fields in economics. An axiomatic study begins with the specification of a domain of problems, and the formulation of a list of desirable properties (axioms) of solutions for the domain, whereas it ends with (as complete as possible) descriptions of the families of solutions satisfying various combinations of the properties (e.g., Thomson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Essa abordagem também foi apropriada por Bleichrodt 13 que, em síntese e sob uma diferente perspectiva, definiu um algoritmo para eqüida-de, tanto na perspectiva da utilidade como na condição de saúde (capabilities). O algoritmo tem como base a eqüidade ex-post (distribuição final de QALYs), a eqüidade ex-ante (com justo processo de alocação de QALYs) e a teoria da utilidade multiatributiva, como base para dirimir o trade-off.…”
Section: Metodologiaunclassified